2013
DOI: 10.1089/jwh.2012.4039
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Clinically Significant Insomnia Among Pregnant Low-Income Latinas

Abstract: Background: Poor sleep, common during pregnancy, is associated with negative health risks. The study aimed to identify predictors of clinically significant insomnia among pregnant Latinas. Methods: A total of 1289 pregnant Latinas recruited from obstetric clinics completed the Insomnia Severity Index (ISI) and questions about demographics and sleep. Results: Clinically significant insomnia (ISI ‡ 10) was present among 17% of participants. Significant correlates of clinically significant insomnia were higher sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 82 publications
1
28
1
Order By: Relevance
“…Links between subjective sleep and negative mood were previously found in nonpregnant samples (Alvaro et al 2013;Manber and Chambers 2009), as well as among pregnant (Manber et al 2013;Skouteris et al 2008;Skouteris et al 2009a) and postpartum (Goyal et al 2009;Wolfson et al 2003) women. However, links between objective sleep disturbances and the two measures of emotional distress in the present study were not significant.…”
Section: Sleep and Emotional Distressmentioning
confidence: 77%
See 2 more Smart Citations
“…Links between subjective sleep and negative mood were previously found in nonpregnant samples (Alvaro et al 2013;Manber and Chambers 2009), as well as among pregnant (Manber et al 2013;Skouteris et al 2008;Skouteris et al 2009a) and postpartum (Goyal et al 2009;Wolfson et al 2003) women. However, links between objective sleep disturbances and the two measures of emotional distress in the present study were not significant.…”
Section: Sleep and Emotional Distressmentioning
confidence: 77%
“…Pregnancy is characterized by substantial changes in sleep patterns, such as increased frequency of insomnia symptoms, including night-wakings, daytime fatigue, and in some cases, also difficulties falling asleep and waking up too early in the morning (Manber et al 2013;Mindell and Jacobson 2000;Skouteris et al 2009a;Tsai et al 2012). Although most of the studies in this field are based on self-reported measures of sleep, studies that used objective sleep measures, such as actigraphy and polysomnography (PSG), support these findings and suggest that in comparison to nonpregnant women, pregnant women have lower sleep efficiency, more frequent night-wakings and longer night-wakings and spend more time in light sleep and less time in deep sleep and REM sleep (Hertz et al 1992;Wilson et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…She may experience increased levels of stress and distress. 44,91 All of these influences may disrupt sleep. However, we contend that an emphasis regarding sleep concerns should be placed on the first 20 w gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Swanson et al 42 reported that 45% of pregnant women scored above the threshold value, and Fernandez-Alonso et al 43 identified more than 73% in late pregnancy. Manber and colleagues, 44 however, reported that only 17% of Latina women, across all trimesters, met criteria for insomnia (≥ 10) and that there was no difference across trimesters.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%